Learning by disinflating - Ellison, M; Ellison, M; Barnett, A (University of Oxford, 2011)
Disinflationary episodes are a valuable source of information for economic agents trying to learn about the economy. This paper is especially interested in how a policymaker can themselves learn by disinflating. The approach differs from the existing literature, which typically focuses on the learning of private agents during a disinflation. We build a model where both the policymaker and private agents learn, and ask what happens if the poicymaker has to disinflate to satisfy a new central bank mandate specifying greater emphasis on inflation stabilisation. In this case, our results show that inflation may fall dramatically before it gradually rises to its new long run level. The potential for inflation to undershoot its long run level during a disinflationary episode suggests that caution should be exercised when assessing the success of any change in the policymaker's mandate.